Interrelated ecological impacts of climate change on an apex predator. Issue 4 (4th February 2020) - Laidre, Kristin L.; Atkinson, Stephen; Regehr, Eric V.; Stern, Harry L.; Born, Erik W.; Wiig, Øystein; Lunn, Nicholas J.; Dyck, Markus
Abstract: Climate change has broad ecological implications for species that rely on sensitive habitats. For some top predators, loss of habitat is expected to lead to cascading behavioral, nutritional, and reproductive changes that ultimately accelerate population declines. In the case of the polar bear ( Ursus maritimus ), declining Arctic sea ice reduces access to prey and lengthens seasonal fasting periods. We used a novel combination of physical capture, biopsy darting, and visual aerial observation data to project reproductive performance for polar bears by linking sea ice loss to changes in habitat use, body condition (i.e., fatness), and cub production. Satellite telemetry data from 43 (1991–1997) and 38 (2009–2015) adult female polar bears in the Baffin Bay subpopulation showed that bears now spend an additional 30 d on land (90 d in total) in the 2000s compared to the 1990s, a change closely correlated with changes in spring sea ice breakup and fall sea ice formation. Body condition declined for all sex, age, and reproductive classes and was positively correlated with sea ice availability in the current and previous year. Furthermore, cub litter size was positively correlated with maternal condition and spring breakup date (i.e., later breakup leading to larger litters), and negatively correlated with the duration of the ice‐free period (i.e., longer ice‐free periods leading to smaller litters). Based on these relationships, we projected reproductive performance three polar bear generations into the future (approximately 35 yr). Results indicate that two‐cub litters, previously the norm, could largely disappear from Baffin Bay as sea ice loss continues. Our findings demonstrate how concurrent analysis of multiple data types collected over long periods from polar bears can provide a mechanistic understanding of the ecological implications of climate change. This information is needed for long‐term conservation planning, which includes quantitative harvest risk assessments that incorporate estimated or assumed trends in future environmental carrying capacity.